Successful Management of Repetitive Urinary Obstruction and Anuria Caused by Double J Stent Calculi Formation after Renal Transplantation - Zongyao Hao; Li Zhang; Jun Zhou; Xiansheng Zhang; Haoqiang Shi; Yifei Zhang; Pengfei Wei; Chaozhao Liang (Case Reports in Transplantation)
This report firstly describes an extremely rare case of repetitive double J stent calculi formation after renal transplantation caused by the antihyperparathyroidism (HPT) drug calcitriol. In 2012, a woman initially presented to our hospital for anuria with lower abdominal pain. She was diagnosed with allograft hydronephrosis and double J stents obstruction by calculi formation after transplantation and treated with triplicate stents replacements in another hospital without clinical manifestations improvements. Through detailed exploration of medical history, we conclude that the abnormal calculi formation is due to the calcitriol (1,25-dihydroxyvitamin D3) administration, a drug which can increase renal tubular reabsorption of calcium for treating posttransplant HPT bone disease. After discontinuing calcitriol, the patient was stone-free and had a good recovery without severe complications during the 9-month follow-up. Our novel findings may provide an important clue and approach to managing formidable repetitive double J stent calculi formation in the clinical trial.